THE IMPACT OF DENTAL IMPLANT DIAMETER AND LENGTH ON OVERALL FAILURE RATES REGARDING DELAYED LOADING PROTOCOL - Constantin Razvan Giuvara; Cosmin Bida; Ovidiu Nicolaiciuc; Bogdan Bulancea; Eduard Radu Cernei; Doriana Agop-Forna; Dan-Nicolae Bosanceanu (Romanian Dental Association for Education, 2020)
The study is aimed at evaluating the importance of physical characteristics of dental implants like diameter and length in relation to the overall failure rate. MATERIAL AND METHOD: The relevant data was obtained from analyzing the failure rates of dental implants used to rehabilitate the clinical condition of the study group's patients and which added up to a number of 124 implants. RESULTS AND DISCUSSIONS: The overall implant fail rate was established to be 8.06% meaning a total number of 10 implants that were considered to be a clinical failure. All of the implants that were considered to be clinical failure were associated with small diameters and/or lengths. CONCLUSIONS: The clinical length and diameter of the implant has been proved to enhance the success rate of the dental implant inside the low-density bone